Recent Publications Upon Economics (Quarterly Journal of Economics, 1907)
Journal Article Recent Publications Upon Economics Get access The Quarterly Journal of Economics, Volume 21, Issue 4, August 1907, Pages 659–671, https://doi.org/10.1093/qje/21.4.659 Published: 01 August 1907